SNAKE BITE RESCUE TRAINING: AN EFFORT TO IMPROVE INJURY MANAGEMENT SKILLS IN MENYUNYUR VILLAGE, GRABAGAN DISTRICT, TUBAN REGENCY - Faqih, Moh. Ubaidillah; Ferianto, Kusno; Karyo; moh ubaidillah (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Background: Snake bites are an emergency issue frequently occurring in rural areas, particularly in forested environments, and can lead to serious injuries, disabilities, and even death. High mortality rates from snake bites are often due to a lack of knowledge and skills in handling these incidents. Method: A Snake Bite Rescue training was conducted over 7 days in Desa Menyunyur, Kecamatan Grabagan, Kabupaten Tuban. This training involved 10 local farmers and consisted of three main phases: initial data assessment, intensive training, and final evaluation. The training methods included lectures, demonstrations, and simulations of snake bite management. Result: The training results showed a significant improvement in participants' knowledge and skills in managing snake bites, as well as an increased awareness of preventive measures. Conclusion: This training is expected to contribute to a reduction in serious injuries and deaths from snake bites and to enhance the safety of farmers in the area.